New and poorly known Palaearctic fungus gnats (Diptera, Sciaroidea) - Jukka Salmela; Levente-Péter Kolcsár (PENSOFT PUBLISHERS, 2022)
Background
Fungus gnats (Sciaroidea) are a globally species rich group of lower Diptera. In Europe, Fennoscandian peninsula in particular holds a notable diversity, ca. 1000 species, of which 10 % are still unnamed. Fungus gnats are predominantly terrestrial insects, but some species dwell in wetland habitats.
New information
Eight new fungus gnat species, belonging to the families Keroplatidae (Orfelia boreoalpina Salmela sp.n.) and Mycetophilidae (Sciophila holopaineni Salmela sp.n., S. curvata Salmela sp.n., Boletina sasakawai Salmela & Kolcsar sp.n., B. norokorpii Salmela & Kolcsar sp.n., Phronia sompio Salmela sp.n., P. reducta Salmela sp.n., P prolongata Salmela sp.n.), are described. Four of the species are known from Fennoscandia only whilst two are supposed to have boreo-alpine disjunct ranges, i.e. having populations in Fennoscandia and the Central European Alps. One of the species probably has a boreal range (Finnish Lapland and Central Siberia). Type material of Boletina curta Sasakawa & Kimura from Japan was found to consist of two species, and a further species close to these taxa is described from Finland. Phronia elegantula Hackman is redescribed and reported for the first time from Norway. DNA barcodes are provided for the first time for five species.